The Sector Bias of Skill-biased Technical Change and the Rising Skill Premium in Transition Economies - Piero Esposito; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2007)
In this paper we test the hypothesis that the sector bias of skill-biased technical change is important in explaining the rising relative wage of skilled workers in the manufacturing sector in three Central and Eastern European transition countries. The evidence for Hungary and Poland is consistent with the sector bias being important in explaining the rising wage premium; the hypotheses is however not confirmed for the Czech Republic.
Keywords: C62; C68; F16; O33; 330; skill premium; factor prices; biased technical change; transition